Donating time or money: Are they substitutes or complements? - Bastian Hartmann; Martin Werding (Center for Economic Studies and ifo Institute (CESifo), 2012)
Decisions to donate time or money for charitable purposes are typically seen as make-or-buy decisions, implying that there should be a clear distinction between individuals engaging in one of these two forms of giving and that this distinction should be somehow linked to opportunity costs. But this is not at all what we observe in micro-level data. We therefore suggest an alternative explanation by which time and cash donations are complements rather than substitutes. Assuming that there is asymmetric information about charities' activities and their effectiveness, doing volunteer work may serve as a screening mechanism enabling donors to better assess the use that is made of the money they could contribute. We formalize this idea and, building on the European Social Survey (ESS), we also provide empirical evidence regarding the co-variation of volunteering and donating money which is suited to support our view.
Keywords: D64; D82; J22; L31; 330; charities; cash donations; volunteer work; asymmetric information; screening; empirical evidence; Wohltätigkeit; Spende; Asymmetrische Information; Signalling; Ehrenamtliche Arbeit; Komplementärgut; Theorie; Schätzung; EU-Staaten